Ariadne : Almanach des Archivs der deutschen Frauenbewegung. (Kassel : Archiv der deutschen Frauenbewegung.)
Fonds Suzan Daniel (FSD)
Periodiciteit : halfjaarlijks
Redactie : Gottschalkstrasse 57, 34127 Kassel
Duits
Periodiek